2019
DOI: 10.1021/acssensors.9b00686
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed DNA Identification Using Site Specific dCas9 Barcodes and Nanopore Sensing

Abstract: Decorating double-stranded DNA with dCas9 barcodes to identify characteristic short sequences provides an alternative to fully sequencing DNA samples for rapid and highly specific analysis of a DNA sample. Solid-state nanopore sensors are especially promising for this type of single-molecule sensing because of the ability to analyze patterns in the ionic current signatures of DNA molecules. Here, we systematically demonstrate the use of highly specific dCas9 probes to create unique barcodes on the DNA that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…As a result, almost half of the overall waste reduction accounts for a 35% percent drop in the garbage disposal, and the other half is for recycling. This finding is consistent with the US surrender program, which reduces municipal waste by 25-35% for disposal [110].…”
Section: Rfid Transponders On Curbside Waste and Recycling Binssupporting
confidence: 87%
“…As a result, almost half of the overall waste reduction accounts for a 35% percent drop in the garbage disposal, and the other half is for recycling. This finding is consistent with the US surrender program, which reduces municipal waste by 25-35% for disposal [110].…”
Section: Rfid Transponders On Curbside Waste and Recycling Binssupporting
confidence: 87%
“…Using nanopores as a sensing strategy enables detection of dsDNA without unzipping or temperature changes and also opens up opportunities for multiplexing. Yang et al showed that the binding position of the dCas9 effector protein could be deduced from the ionic current spike, which was later also confirmed by Weckman et al ( Weckman et al, 2019 ; Yang et al, 2018 ). The latter authors designed multiple crRNA sequences for dCas9 that could all bind to the same DNA sequence, creating ‘barcodes’ in the ionic current traces specific for the different DNA sequences.…”
Section: Crispr/cas Sensing In Poc Sensorsmentioning
confidence: 66%
“…Several sensor types have been created by researchers so far, in which no target-amplification is needed to measure at a very low LOD. These sensors are a graphene-based field effect transistor (gFET) ( Hajian et al, 2019 ), nanopore sensors ( Weckman et al, 2019 ; Yang et al, 2018 ), electrochemical sensors ( Bruch et al, 2019 ; Dai et al, 2019 ; Xu et al, 2020 ; D. Zhang et al, 2020 ) and a conductivity sensor combined with a DNA gel ( English et al, 2019 ).…”
Section: Crispr/cas Sensing In Poc Sensorsmentioning
confidence: 99%
“…Toward the ultimate goal of integrating the different functional molecules into the specific sites of the circuit, the selective fabrication of single-molecule junction remained as one of the critical steps but remained unexplored, while the control of the interaction between the molecule and electrodes will offer a unique opportunity. [1,2] The control over the interaction between molecule and electrode promises to vast applications in numerous subjects, such as catalysis, [3,4] materials, [5][6][7] sensors, [8][9][10][11] molecular biology, [12][13][14][15] and bottom-up devices. [16,17] In recent years, the single-molecule conductance measurement technique has witnessed significant progress in surface science, that an…”
Section: Doi: 101002/smll202004720mentioning
confidence: 99%